2009
DOI: 10.1007/s00125-009-1467-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of modification of dietary protein intake on the progression of diabetic nephropathy: a randomised controlled trial

Abstract: Aims/hypothesis There is currently insufficient evidence to recommend a low-protein diet for type 2 diabetic patients with diabetic nephropathy. We assessed whether a low-protein diet could prevent the progression of diabetic nephropathy. Methods This was a multi-site parallel randomised controlled trial for prevention of diabetic nephropathy progression among 112 Japanese type 2 diabetic patients with overt nephropathy. It was conducted in Japan from 1 December 1997 to 30 April 2006. The participants were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 36 publications
1
55
1
Order By: Relevance
“…Regarding diet therapy, the efficacy of a low-protein diet (LPD) for advanced diabetic nephropathy remains controversial [2]. Previous clinical studies have not consistently shown beneficial effects of an LPD for the preservation of renal function in diabetic nephropathy [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding diet therapy, the efficacy of a low-protein diet (LPD) for advanced diabetic nephropathy remains controversial [2]. Previous clinical studies have not consistently shown beneficial effects of an LPD for the preservation of renal function in diabetic nephropathy [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nezu et al showed that an LPD for diabetic nephropathy improves the estimated glomerular filtration rate when patients adhere to a protein-restricted diet [11]. However, LPD adherence is often poor [3,11], which has contributed to the controversial results of previous clinical studies. In addition, the amount of protein restriction would be expected to be important for renoprotection.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] A low-protein diet has not reduced the risk of mortality or ESRD compared with a usual protein diet, at least in the course of CKD stages 1-3. [35][36][37][38][39] Screening for patients with chronic kidney disease stage 1-3: facts and fallacies…”
Section: Methods Of Researchmentioning
confidence: 99%
“…24 In addition, an observational study of the general Japanese population showed that the higher-protein diet group had a lower odds ratio of chronic kidney disease, 25 and an intervention study did not prove the effectiveness of the low-protein diet. 26 Furthermore, the Modification of Diet in Renal Disease study, a famous randomized controlled trial in the United States, compared the low-protein diet and extremely low-protein diet in subjects with renal dysfunction and found that there was no significant difference in the time to end-stage renal failure (requiring hemodialysis or kidney transplantation) between the two diet groups, and that the extremely low-protein diet group had a higher mortality rate. 27 After the results were reported in 2009, Ikizler summarized the advantages and disadvantages of the low-protein diet; the details are shown in Table 2.…”
Section: Low-protein Dietmentioning
confidence: 99%